Assessing quality of maternity care in Hungary: expert validation and testing of the mother-centered prenatal care (MCPC) survey instrument - Nicholas Rubashkin; Imre Szebik; Petra Baji; Zsuzsa Szántó; Éva Susánszky; Saraswathi Vedam (BMC, 2017)
Abstract Background Instruments to assess quality of maternity care in Central and Eastern European (CEE) region are scarce, despite reports of poor doctor-patient communication, non-evidence-based care, and informal cash payments. We validated and tested an online questionnaire to study maternity care experiences among Hungarian women. Methods Following literature review, we collated validated items and scales from two previous English-language surveys and adapted them to the Hungarian context. An expert panel assessed items for clarity and relevance on a 4-point ordinal scale. We calculated item-level Content Validation Index (CVI) scores. We designed 9 new items concerning informal cash payments, as well as 7 new "model of care" categories based on mode of payment. The final questionnaire (N = 111 items) was tested in two samples of Hungarian women, representative (N = 600) and convenience (N = 657). We conducted bivariate analysis and thematic analysis of open-ended responses. Results Experts rated pre-existing English-language items as clear and relevant to Hungarian women's maternity care experiences with an average CVI for included questions of 0.97. Significant differences emerged across the model of care categories in terms of informal payments, informed consent practices, and women's perceptions of autonomy. Thematic analysis (N = 1015) of women's responses identified 13 priority areas of the maternity care experience, 9 of which were addressed by the questionnaire. Conclusions We developed and validated a comprehensive questionnaire that can be used to evaluate respectful maternity care, evidence-based practice, and informal cash payments in CEE region and beyond.